Anthropogenic Carbon Increase has Caused Critical Shifts in Aragonite Saturation Across a Sensitive Coastal System. Issue 7 (28th June 2022) - Jarníková, Tereza; Ianson, Debby; Allen, Susan E.; Shao, Andrew E.; Olson, Elise M.
Abstract: Estuarine systems host a rich diversity of marine life that is vulnerable to changes in ocean chemistry due to addition of anthropogenic carbon. However, the detection and impact of secular carbon trends in these systems is complicated by heightened natural variability as compared to open‐ocean regimes. We investigate biogeochemical changes between the pre‐industrial (PI) and modern periods using a high‐resolution, three‐dimensional, biophysical model of the Salish Sea, a representative Northeast Pacific coastal system. While the seasonal amplitude of the air‐sea difference in pCO 2 has increased on average since pre‐industrial times, the net CO2 source has changed little. Our simulations show that inorganic carbon has increased throughout the model domain by 29–39 mmol m −3 (28–38 µmol kg −1 ) from the pre‐industrial to present. While this increase is modest in a global context, the region's naturally high inorganic carbon content and the low buffering capacity of the local carbonate system amplify the resultant effects. Notably, this increased carbon drives the estuary toward system‐wide undersaturation of aragonite, negatively impacting shell‐forming organisms. Undersaturation events were rare during the pre‐industrial experiment, with 10%–25% of the domain undersaturated by volume throughout the year, while under present‐day conditions, the majority (55%–75%) of the system experiences corrosive, undersaturated conditions year‐round. These results are extended using recent global coastal observations to show that estuaries throughout the Pacific Rim have already undergone a similar saturation state regime shift. Plain Language Summary: The coastal ocean hosts rich ecosystems which are critical to marine organisms and people and sensitive to human‐caused climate change. We used a detailed computer simulation to understand the carbon cycle in a complex, productive North Pacific coastal system that is fed by a large un‐dammed river, has connecting fjords, and narrows that have strong tides. We determine how much extra carbon has entered the system since the beginning of the industrial revolution. This increase is important because extra carbon in the ocean makes it harder for animals to build shells and structures. We find that large chemical changes have occurred. In fact, we are surprised to find that an important threshold under which shells dissolve has already been crossed in most of the region. We consider observations from other global coastal oceans and find that this same threshold may have been crossed throughout coastal oceans in much of the Pacific, and that this shift will likely become prominent in the Atlantic Ocean by 2080. Key Points: On average, dissolved inorganic carbon has increased by 29–39 mmol m −3 in the Salish Sea, causing a shift to majority aragonite undersaturation by volume Modern aragonite saturation conditions, though variable, are typically outside of the range of pre‐industrial values throughout the domain Much of the coastal Pacific Rim has similar carbonate chemistry conditions, and comparable shifts in aragonite saturation may have occurred